2014
DOI: 10.1016/j.euprot.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis reveals characteristic molecular changes accompanying the transformation of nonmalignant to cancer lung cells

Abstract: © 2014 The Authors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Numerous studies are focused on the role of ZYX as a component of focal adhesions and the cytoskeleton, and as a mechanosensor. It is commonly known that changes in the expression of cytoskeleton-organising proteins have an impact on cell migration, which is important in metastasis (9,23). Not only for this reason, but also for its abovementioned features, the role of ZYX in carcinogenesis is getting much attention from researchers.…”
mentioning
confidence: 99%
“…Numerous studies are focused on the role of ZYX as a component of focal adhesions and the cytoskeleton, and as a mechanosensor. It is commonly known that changes in the expression of cytoskeleton-organising proteins have an impact on cell migration, which is important in metastasis (9,23). Not only for this reason, but also for its abovementioned features, the role of ZYX in carcinogenesis is getting much attention from researchers.…”
mentioning
confidence: 99%
“…
of hemoproteins are increased in cancer vs. normal cells (Table 1) [8]. We found that the levels of proteins involved in both heme biosynthesis (ALAS1) and heme uptake (HCP1 and HRG-1), and the levels of oxygen-utilizing hemoproteins, such as cytochromes and cytoglobins, are upregulated in NSCLC cells compared to normal cells [10].
…”
mentioning
confidence: 72%
“…Therefore, in the current study, we set out to deconstruct the contribution of individual tumor suppressor gene (TSG) mutation toward glioma initiation and progression, using the MADM system ( Figure 2a). The identification of OPCs as the glioma cell of origin also provides a unique opportunity to investigate signaling aberrations at distinct stages of tumor progression, since we can use the OPC-specific surface marker PDGFRa to purify both pretransforming mutant OPCs (PreT-OPCs) and malignant tumor cells for signaling analysis (Cadinu et al, 2014;Watson et al, 2013;Maglietta et al, 2012;Gorgoulis et al, 2005). The identification of OPCs as the glioma cell of origin also provides a unique opportunity to investigate signaling aberrations at distinct stages of tumor progression, since we can use the OPC-specific surface marker PDGFRa to purify both pretransforming mutant OPCs (PreT-OPCs) and malignant tumor cells for signaling analysis (Cadinu et al, 2014;Watson et al, 2013;Maglietta et al, 2012;Gorgoulis et al, 2005).…”
mentioning
confidence: 99%
“…We hypothesized that p53 mutation and NF1 mutation might play distinct roles to promote gliomagenesis: the deletion of one could promote proliferation while the deletion of the other could cripple differentiation, thereby cooperatively leading to tumor formation ( Figure 1d). The identification of OPCs as the glioma cell of origin also provides a unique opportunity to investigate signaling aberrations at distinct stages of tumor progression, since we can use the OPC-specific surface marker PDGFRa to purify both pretransforming mutant OPCs (PreT-OPCs) and malignant tumor cells for signaling analysis (Cadinu et al, 2014;Watson et al, 2013;Maglietta et al, 2012;Gorgoulis et al, 2005). Since NF1 is known as a RasGAP (Klose et al, 1998;Shin et al, 2012;Scheffzek et al, 1998;Morcos, Thapar, Tusneem, Stacey, & Tamanoi, 1996), we focused our analysis on the downstream effectors of the Ras pathway to examine the route of progressive activation of these molecules from pre-malignant to malignant stages (Figure 1e).…”
mentioning
confidence: 99%